Penerapan Metode Demster Shafer Pada Sistem Pakar Terhadap Penyakit Rabies Hewan - Togar Timoteus Gultom (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
Dogs (Canis Lupus Familiaris) are one of the pets that are liked by humans because they are easy to adjust and can make friends. Zoonoses are infectious diseases from animals to humans but from about 200 types of zoonoses or parasites that are transmitted by animals. Rabies disease, Campylobacteriosis, skin disease, Toxocariasis, are some of the diseases that can be transmitted by dogs. Dog owners sometimes do not understand when disease strikes their dog. Dog owners usually treat them in their own way without paying attention to their health and not being balanced with knowledge about handling dog diseases. Prevention of disease transmission must be balanced with knowledge of dog owners about the types of dog diseases and knowledge of the symptoms that appear in dogs to determine whether the dog is positive for the disease or not. In today's world of health, there is an information system where the system has the ability to solve problems like experts. The information system is called the Expert System.